2022
DOI: 10.3389/fphar.2022.934256
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic targets by traditional Chinese medicine for ischemia-reperfusion injury induced apoptosis on cardiovascular and cerebrovascular diseases

Abstract: Traditional Chinese medicine (TCM) has a significant role in treating and preventing human diseases. Ischemic heart and cerebrovascular injuries are two types of diseases with different clinical manifestations with high prevalence and incidence. In recent years, it has been reported that many TCM has beneficial effects on ischemic diseases through the inhibition of apoptosis, which is the key target to treat myocardial and cerebral ischemia. This review provides a comprehensive summary of the mechanisms of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 110 publications
0
0
0
Order By: Relevance
“…Experiments to fully characterize this effect are ongoing. Results at the time of this writing are particularly encouraging since the robust suppression of inflammatory tissue damage has been demonstrated for turmeric [ 46 ], ginger [ 47 , 48 ], capsicum/capsaicin—in red pepper [ 49 , 50 ], paprika [ 51 , 52 ], and nutmeg [ 53 , 54 , 55 ] as described in Section 2 of this report. In summary, the research described here describes the current understanding of cardiovascular diseases and approaches to its management, and explores novel strategies for the use of GRAS natural medical materials to potentiate clinical efficacy and reduce the toxicity of currently used therapies for CVDs.…”
Section: Future Directionsmentioning
confidence: 75%
See 2 more Smart Citations
“…Experiments to fully characterize this effect are ongoing. Results at the time of this writing are particularly encouraging since the robust suppression of inflammatory tissue damage has been demonstrated for turmeric [ 46 ], ginger [ 47 , 48 ], capsicum/capsaicin—in red pepper [ 49 , 50 ], paprika [ 51 , 52 ], and nutmeg [ 53 , 54 , 55 ] as described in Section 2 of this report. In summary, the research described here describes the current understanding of cardiovascular diseases and approaches to its management, and explores novel strategies for the use of GRAS natural medical materials to potentiate clinical efficacy and reduce the toxicity of currently used therapies for CVDs.…”
Section: Future Directionsmentioning
confidence: 75%
“…It is nevertheless interesting to note that, during the past decade, the personal utilization of risk reduction strategies available through public education has resulted in some abatement of mortality rates in affluent societies. This includes, prominently, an awareness of the benefits to general health of the dietary intake of polyphenols, especially in flavonoid-rich foods, and flavorings such as the spices described in the present report [ 5 , 6 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Cardiovascular Diseases (Cvds) and Ischemia-reperfusion: A P...mentioning
confidence: 82%
See 1 more Smart Citation
“…5 Traditional Chinese Medicine (TCM) has been proven to be an effective therapeutic option for cerebrovascular diseases. [6][7] Angong Niuhuang Pill (ANP) 安宫牛黄丸 is one of the most wellknown traditional Chinese patent medicines used in the clinical emergency treatment of cardiocerebrovascular diseases. Originating from the Qing Dynasty, it has a history of several hundred years.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an increasing number of pharmacological studies have demonstrated the efficacy of TCM in the prevention and treatment of cardiovascular diseases [6][7][8].…”
Section: Introductionmentioning
confidence: 99%